A New SiC Planar-Gate IGBT for Injection Enhancement Effect and Low Oxide Field - Meng Zhang; Baikui Li; Zheyang Zheng; Xi Tang; Jin Wei (Energies, 2020)
A new silicon carbide (SiC) planar-gate insulated-gate bipolar transistor (IGBT) is proposed and comprehensively investigated in this paper. Compared to the traditional SiC planar-gate IGBT, the new IGBT boasts a much stronger injection enhancement effect, which leads to a low on-state voltage (VON) approaching the SiC trench-gate IGBT. The strong injection enhancement effect is obtained by a heavily doped carrier storage layer (CSL), which creates a hole barrier under the p-body to hinder minority carriers from being extracted away through the p-body. A p-shield is located at the bottom of the CSL and coupled to the p-body of the IGBT by an embedded p-MOSFET (metal-oxide-semiconductor field effect transistors). In off-state, the heavily doped CSL is shielded by the p-MOSFET clamped p-shield. Thus, a high breakdown voltage is maintained. At the same time, owing to the planar-gate structure, the proposed IGBT does not suffer the high oxide field that threatens the long-term reliability of the trench-gate IGBT. The turn-off characteristics of the new IGBT are also studied, and the turn-off energy loss (EOFF) is similar to the conventional planar-gate IGBT. Therefore, the new IGBT achieves the benefits of both the conventional planar-gate IGBT and the trench-gate IGBT, i.e., a superior VON-EOFF trade-off and a low oxide field.